PENGARUH METODE DEMONSTRASI TERHADAP PEMBELAJARAN DRAMA DI KELAS XI SMA NEGERI 1 X KOTO TANAH DATAR - Adip, Ahmad; Syeilendra (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to determine the effect of cultural arts learning (drama) using the demonstration method on theater learning in class XI F 5 at SMA Negeri 1 X Koto. The type of research used is quantitative research with an experimental method. The population in this study is all eleventh-grade students at SMA Negeri 1 X Koto for the 2024/2025 academic year, totaling 164 students, with a sample of 68 students. The research instruments were the researchers themselves, assisted by writing tools and a camera. Data were collected through observation, tests (pretest and posttest), documentation, and literature study. The data were analyzed using normality tests, Wilcoxon Signed Rank Test, and Mann–Whitney U Test. The research results show that there is a significant difference between students' learning outcomes before and after learning in the experimental class, and there is a significant difference between the posttest results of the control class and the experimental class. Thus, the working hypothesis (H₁) stating that the demonstration method affects the improvement of students' drama learning outcomes can be accepted, while the null hypothesis (H₀) is rejected. These findings confirm that the demonstration method is effective for use in teaching drama at the high school level. The improvement in students' learning outcomes in the experimental class is due to the characteristics of the demonstration method, which provides students with the opportunity to directly observe examples of dialogue interpretation, expression, and role-playing techniques. Through observation and hands-on practice, students find it easier to understand the learning material, engage actively, and can develop their drama art skills more optimally. This condition makes the learning process more meaningful and has a positive impact on students' learning outcomes.